UJI KANDUNGAN BAKTERI Escherichia coli DALAM PRODUK OBAT TRADISIONAL YANG DIJUAL DI PASAR BERINGHARJO - Ken Zaim Arifin; Nanik Sulistyani (Jurnal Fitofarmaka Indonesia, 2023)
Indonesian traditional medicine has long been known and used by the community in maintaining health and treating illnesses. Identification of Escherichia coli bacteria was chosen because this bacterium is an indicator of sanitation and an unsanitary environment in the process of making traditional medicines. The purpose of this study was to determine the contamination of Escherichia coli bacteria in traditional medicines sold at the Beringharjo Traditional Market. This study was an experimental study. The sampling technique in this study was purposive sampling. culture technique on Echerichiae coli bacteria using TBX Agar Media and the Total Plate Number test using PCA. Bacterial analysis can be done by observing the culture media and test media on traditional medicine samples. The results of the ALT values were 70 ± 14,1 x 101  CFU/ml to 14,9 ± 1,2  x 105  CFU/ml and the Escherichia Coli Identification Test was negative or 0 colonies/g. the specified conditions refer to PerBPOM No. 32 of 2019. It can be concluded that in the ALT test of ten products, 80% of them have met the requirements and 20% of them do not meet the requirements. In the Escherichia Coli Identification Test, out of ten samples, all 100% of the samples met the requirements.